2015
DOI: 10.1111/1756-185x.12592
|View full text |Cite
|
Sign up to set email alerts
|

SLE myopathy: a clinicopathological study

Abstract: Histological evidence of myositis was found in 46.66% of SLE patients and there were no significant differences in clinical/laboratory features in patients with or without myositis. Type 2 atrophy was seen in patients irrespective of time of the biopsy, treatment received and presence or absence of myositis. Type 2 atrophy was considered the major cause for muscle symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The association of myositis and SLE has been previously explored by several authors [2,15], showing that muscle involvement in SLE patients in the form of diffuse pain or muscular weakness is relatively frequent. A study reported that of 7 SLE patients with myositis, 3 had muscle weakness [15].…”
Section: Discussionmentioning
confidence: 99%
“…The association of myositis and SLE has been previously explored by several authors [2,15], showing that muscle involvement in SLE patients in the form of diffuse pain or muscular weakness is relatively frequent. A study reported that of 7 SLE patients with myositis, 3 had muscle weakness [15].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment remains empirical and includes steroids and/or immunosuppressants, intravenous immunoglobulins, biological factors, and rituximab [16]. Diaphragmatic muscle involvement and related weakness may present as ‘shrinking lungs and high sluggish diaphragm with clear lung fields' in lupus occurring mainly in patients without evidence of systemic myopathy [144,145,146,147,148]. In such a clinical context, hypercapnic respiratory failure has occasionally been reported [149].…”
Section: Acute Hypercapnic Respiratory Failure Related To Acute Ventimentioning
confidence: 99%
“…Clinical evidence of myositis was present in 8.8% of SLE patients in registry. [19] Two patients of dengue fever who showed spontaneous activity underwent biopsy. Both of them had normal study.…”
Section: Discussionmentioning
confidence: 99%